2010
DOI: 10.3324/haematol.2010.035329
|View full text |Cite
|
Sign up to set email alerts
|

Recipient lymphocyte infusion in MHC-matched bone marrow chimeras induces a limited lymphohematopoietic host-versus-graft reactivity but a significant antileukemic effect mediated by CD8+ T cells and natural killer cells

Abstract: BackgroundChallenge of MHC-mismatched murine bone marrow chimeras with recipient-type lymphocytes (recipient lymphocyte infusion) produces antileukemic responses in association with rejection of donor chimerism. In contrast, MHC-matched chimeras resist eradication of donor chimerism by recipient lymphocyte infusion. Here, we investigated lymphohematopoietic host-versus-graft reactivity and antileukemic responses in the MHC-matched setting, which is reminiscent of the majority of clinical transplants. Design an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…A similar observation has been made in mice and humans with hematologic malignancies undergoing allogeneic stem cell transplantation. In the animal model, depletion of donor NK cells abrogated anti-leukemia effects of donor T cells (31). In humans, early donor derived NK cell recovery has been shown to be associated with a lower relapse risk in the non-myeloablative setting in the recipients of T cell replete allografts (32).…”
Section: Discussionmentioning
confidence: 99%
“…A similar observation has been made in mice and humans with hematologic malignancies undergoing allogeneic stem cell transplantation. In the animal model, depletion of donor NK cells abrogated anti-leukemia effects of donor T cells (31). In humans, early donor derived NK cell recovery has been shown to be associated with a lower relapse risk in the non-myeloablative setting in the recipients of T cell replete allografts (32).…”
Section: Discussionmentioning
confidence: 99%
“…Further studies indicated that CD8 + T cells were the major source of IFN-γ. Invariant/constant natural killer T (NK) T-cells, dendritic cells and NK cells, and the interaction among these different immune cells also participate in the antitumor process (11,22). The above course may be classified as host vs. graft (HVG) effects associated with massive systemic cytokine release.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, depletion of the donor's NK cells abrogated antileukemia effects of the donor's T cells in the recipient of a stem cell transplant (3). NK cell recovery also preceded engraftment and expansion of the donor's T cells (4 1 T cells. We are happy to reply to the questions raised by Dr. Manjili and Dr. Toor regarding potential mechanisms behind our observations.…”
Section: T Cell Priming In the Absence Of Nk Cells Leads To Enhanced mentioning
confidence: 99%
“…In a retrospective study, Panse and col-leagues (6) correlated the percentage of NK cells present in the infused HLA-matched transplant with T cell chimerism in the host, a parameter that is associated with a positive transplantation outcome. In contrast, De Somer and colleagues (4) have developed a mouse model to investigate lymphohematopoietic host-versus-graft reactivity and antileukemic responses in MHC-matched chimeras, a setting that may be reminiscent of the majority of clinical transplants. This study suggests that lymphohematopoietic alloreactivity provoked by adoptively transferred T cells provides a cytokine environment leading to NK cell activation and subsequent NK cellmediated killing of recipient tumor cells.…”
Section: T Cell Priming In the Absence Of Nk Cells Leads To Enhanced mentioning
confidence: 99%